School leadership aspirations of black and minority ethnic teachers - Eweka, Edosa Ulamén (2015)
Studies investigating the career progression of BME teachers identify institutionalised discrimination, social inequality and unfavourable school practices as forces militating against the realisation of their school leadership aspirations. This study adds to this discourse by exploring some mediating forces, shaped by life history, beliefs, values, and workplace reactions, in the realisation of school leadership aspirations. In this regard, this research explores issues relating to the leadership roles a group of BME teachers conceive for themselves and their perceptions of success; the balance of personal, professional and situational factors, and the dynamics between personal agency and workplace structure, all in relation to leadership success. Since this study concerns aspect of life histories, values, beliefs, and workplace reactions, recognition of the utility of qualitative approach was given, and as such the semi-structured interviewing as the method to gain an authentic understanding to these research issues was employed.